Mine-influenced surface water quality at Okaba coal mine: Characterization and constructed wetland management - Adegboye , Ayobami Joshua; Idowu, Kayode Augustine (Journal of Degraded and Mining Lands Management, 2026)
Characterization of mine-influenced surface water quality is essential for effective mine water management. This study characterized the physicochemical quality of surface water at the Okaba coal mine, Ankpa LGA, Kogi State, Nigeria, and proposed a passive constructed wetland treatment system. Water samples from nine upstream, midstream, and downstream stations were analyzed for temperature, pH, electrical conductivity, total dissolved solids, salinity, total hardness, sulphate, biochemical oxygen demand, chemical oxygen demand, and nitrate. Results were compared against World Health Organization and Nigerian regulatory permissible limits. Mean values recorded were: temperature 28.40 ± 0.8 °C, pH 6.93 ± 0.13, electrical conductivity 562.7 ± 2.9 µS/cm, total dissolved solids 358.5 ± 4.2 mg/L, total hardness 672.9 ± 1.6 mg/L, sulphate 57.3 ± 0.6 mg/L, biochemical oxygen demand 100.0 ± 0.8 mg/L, chemical oxygen demand 218.0 ± 2.1 mg/L, and nitrate 29.0 ± 0.8 mg/L. Electrical conductivity, total hardness, biochemical oxygen demand, chemical oxygen demand, and nitrate exceeded permissible limits, signifying contamination from acid mine drainage, organic loading, and mineral leaching. A free water surface constructed wetland was designed using the first-order kinetic model of Kadlec and Wallace (2009). A three-cell system of 4.15 ha with a 14.4-day hydraulic retention time achieved full regulatory compliance for all exceedance parameters. These findings established a hydrogeochemical baseline and demonstrated the feasibility of passive wetland treatment at active Nigerian coal mining sites.